Democratización del Arbitraje en el Perú - Díaz Honores, Jenny (2021)
The purpose of this article is to highlight the development of alternative dispute resolution mechanisms in our country as a result of the crisis in the judicial courts and the high economic and emotional cost of arbitration. In this way, it explains the instruments that the State has implemented in favor of the most vulnerable social sectors to guarantee that the entire population has access to arbitration justice.